THE BLACK MAID’S VOICE IN KATHRYN STOCKETT’S THE HELP - Manguhal Parsaulian Hutagalung; Sri Minda Murni (State University of Medan, 2016)
This study dealt with the Black maid’s voice in Kathryn Stockett’s The Help. Thestudy was conducted by using descriptive qualitative approach. The objectives ofthe study were to find the actions and sayings that the Black maids do and say,and the consequences toward the actions. The data were collected from thenarrations and dialogues in the novel. The study revealed that there are threemultiple resistances that the black maids do in the novel according to Shorter-Gooden and Jones’ theory: ongoing internal coping strategies, ongoing externalcoping strategy, and ongoing specific strategy. The consequences that they facedbefore the publication of the book are: physical abuse, loss of employment,destruction of property, and family’s live. The book was the representative of theirsayings to White people. The responses of White people were analyzed byPeccei’s perlocutionary acts theory and the responses are: White woman threat thewriter and everyone who participated in that book, White woman refused the bookand another one felt happy because everything about her was good in the book.